Currency boards in the Baltic countries: What have we learned? - Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 1999)
Sisällysluettelo: Abstract 5 1 Introduction 6 2 Currency board as an exchange rate arrangement 7 3 A short history of currency board arrangements 10 4 Currency boards in the Baltic countries 12 4.1 Monetary reforms in Estonia and Lithuania 12 4.1.1 Estonia 15 4.1.2 Lithuania 17 4.2 The rnacroeconomic effects of the Baltic currency boards 18 4.2.1 Inflation 20 4.2.2 Output 23 4.3 The Baltic currency boards and financial systems 25 4.4 Assessing the Baltic currency boards 27 5 Concluding remarks 32 References 34 Notes 37 Annex 39
URN:NBN:fi:bof-201408071958
Keywords: 330